Pengaruh Relationship Marketing dan Personal Selling Terhadap Loyalitas Pelanggan Unit Toyota di PT Kartika Sari Mulia Malang - Lucia Eny Rahmawati; Yulis Nurul Aini; Rizky Kurniawan Murtiyanto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Customer loyalty is a key factor in ensuring business sustainability amidst the increasingly competitive automotive industry. This study was prompted by fluctuations in vehicle sales at PT. Kartika Sari Mulia in Malang, highlighting the need to enhance customer loyalty through relationship marketing and personal selling. This study aims to analyse the influence of relationship marketing and personal selling on customer loyalty at PT. Kartika Sari.  This study employed a descriptive quantitative research design with an explanatory research approach. The study sample consisted of 91 respondents selected using purposive sampling. Data were collected via questionnaires, and analysis employed multiple linear regression and hypothesis testing in IBM SPSS Statistics.  The results of the study indicate that Relationship Marketing has a positive and significant effect on customer loyalty, as evidenced by a t-value of 4.361 and a significance level of 0.000 < 0.05. Personal Selling also has a positive and significant effect on customer loyalty, as evidenced by a t-value of 3.579 and a significance level of 0.001 < 0.05. Simultaneously, Relationship Marketing and Personal Selling have a positive and significant effect on customer loyalty, as indicated by a calculated F-value of 76.747 > 3.10 (table F-value) and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.679 indicates that relationship marketing and personal selling account for 67.9% of the variation in customer loyalty. These findings suggest that strengthening relationship marketing and personal selling can enhance customer loyalty at PT Toyota Kartika Sari Mulia Malang.  Based on the research findings, it can be concluded that relationship marketing and personal selling have positive and significant effects on customer loyalty at PT Toyota Kartika Sari Mulia Malang. Therefore, the company is encouraged to strengthen its relationship marketing and personal selling strategies to further enhance customer loyalty.